Bi-layer high-k dielectrics of Al2O3/ZrO2 to reduce damage to MoS2 channel layers during atomic layer deposition. (22nd November 2018) - Woo, Whang Je; Oh, Il-Kwon; Park, Bo-Eun; Kim, Youngjun; Park, Jongseo; Seo, Seunggi; Song, Jeong-Gyu; Jung, Hanearl; Kim, Donghyun; Lim, Jun Hyung; Lee, Sunhee; Kim, Hyungjun
Abstract: To implement two-dimensional (2D) transition metal dichalcogenides (TMDCs) in electric devices, a top-gated device structure is desired. However, there has been possibility of the channel layer being damaged during the upper dielectric deposition process. Because several layers of 2D TMDCs are atomically thin, the damage may significantly degrade the overall electrical performance. In this study, we investigated the damage to molybdenum disulfide (MoS2 ) during the atomic layer deposition (ALD) of single dielectrics of Al2 O3 and ZrO2 . We observed the MoS2 layers were damaged, depending on the ALD process conditions; the kind of oxidant and the growth temperature. To reduce the damage, we formed a bi-layered Al2 O3 /ZrO2 dielectric structure by developing a two-step ALD process. It is notable that the electrical performance of the device was significantly improved compared to those using the single dielectrics, indicating this two-step process is a promising candidate to satisfy the requirements of future 2D TMDCs-based electronics.